2022
DOI: 10.3390/bs12120488
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Demographic, Self-Control, Bullying, Parenting, and Sleep as Proximal Factors Associated with Food Addiction among Adolescents

Abstract: Adolescence is considered an important period of neurodevelopment. It is a time for the emergence of psychosocial vulnerabilities, including symptoms of depression, eating disorders, and increased engagement in unhealthy eating behaviours. Food addiction (FA) in adolescents is an area of study where there has been substantial growth. However, to date, limited studies have considered what demographic characteristics of adolescents may predispose them to endorse greater symptoms of FA. Studies have found a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
1
0
0
Order By: Relevance
“…Specifically, female gender showed a significantly higher probability of FA diagnosis and greater severity compared to males, drawing attention to previous research [i.e., ( 87 , 88 )] highlighting gender differences in addiction tendencies. This result is also supported by Leary et al ( 89 ), who found an association between symptom count and female gender.…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, female gender showed a significantly higher probability of FA diagnosis and greater severity compared to males, drawing attention to previous research [i.e., ( 87 , 88 )] highlighting gender differences in addiction tendencies. This result is also supported by Leary et al ( 89 ), who found an association between symptom count and female gender.…”
Section: Discussionsupporting
confidence: 84%